Aktivering av Border collie : vallningens betydelse för en välmående hund - Rosshagen, Sandra (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
The dog has evolved from the wolf which is the most common species among the predators. The domestication and selection have resulted in different breeds of dogs, which include changed characteristics and personalities. With time, dogs have become more common to have as a pet for different purposes. For example, for hunting, guarding or herding, to name a few. In addition, all dogs have a variety of conducts and needs. Shepherd dogs, such as the Border Collie, require daily mental and physical activation to remain satisfied. Over the years, the main activity for this breed has been herding, but today the Border Collie is used as a working dog, as well as within other types of activities and training. Herding is a genetic behaviour in shepherd dogs. Besides genetics, research has showed that socialization, enriching experiences and environment also play a significant role in their behaviours. The aim with this study is to investigate if the Border Collie can be satisfied, healthy and a happy dog without herding. The result of this study revealed that most Border Collie owners walk their dogs two hours a day, 72% activate their dogs regularly through herding and 56% through obedience. Owners consider their dogs satisfied no matter if they allowed their dogs to herd or not. Both the owners who allowed their dogs to herd and those who did not, experienced behaviour problems with their dogs, for example, an excessive herding of cars, children and bikers. 18% of the owners who let their dogs perform herding, experienced one or more behaviour problems. At the same time, only 8% of the owners who did not let their dogs perform herding, experienced one or more behaviour problems in their dog. One of the most common behaviour problem reported by the owners who practiced herding, was that their dog had a strong urge to herd and a aggressive behaviour. Remaining owners who did not practice herding with their dogs, instead perceived fear to be the main behaviour problem their dog to have.